Depth, tightness and resiliency as market liquidity dimensions: evidence from the Polish stock market. (18th May 2019) - Olbrys, Joanna; Mursztyn, Michal
The aim of this paper is an empirical analysis of market liquidity dimensions on the Warsaw Stock Exchange (WSE). We investigate market depth, tightness, and resiliency for 53 companies divided into three size groups. The high-frequency data covers the period January 2005 - June 2015. The additional goal is a robustness analysis of the results with respect to the whole sample period and three adjacent subsamples: pre-crisis, crisis, and post-crisis periods. Order ratio (OR) is employed as a proxy of market depth. Market tightness is approximated by using relative spread (RS). Market resiliency is estimated by utilising realised spread (RealS). The empirical results indicate that OR values do not depend on a firm size, while RS estimations are slightly higher for small companies. RealS proxy values are positive for almost all stocks. Moreover, the results turn out to be robust to the choice of the sample for all groups of assets.